Chemotaxonomic discrimination of lichen species using an infrared chalcogenide fibre optic sensor: a useful tool for on-field biosourcing. Issue 110 (14th November 2016) - Le Corvec, M.; Boussard-Plédel, C.; Charpentier, F.; Fatih, N.; Le Dare, B.; Massart, F.; Rojas, F.; Tariel, H.; Loréal, O.; Bureau, B.; Boustie, J.; Sire, O.; et al.
Abstract : Spectral analysis of lichen extracts obtained by MIR-FEWS permits to discriminate species and the identification of their major compounds. MIR-FEWS is a rapid, efficient and convenient tool for metabolic profiling. Abstract : Many analytical methods are known to discriminate natural products based on the set of chemical compounds they contain. Here, we evaluated the ability of Fibre Evanescent Wave Spectroscopy (FEWS) to discriminate lichen natural extracts. Ten species of lichens including four chlorolichens (three Cladonia species and Stereocaulon scutelligerum ), three tripartite lichens ( Stereocaulon species) and three cyanolichens ( Lichina pygmaea, Collema cristatum, Peltigera membranacea ) belonging to six genera and six families were studied. One macroscopic cyanobacterium ( Nostoc sp.), corresponding to the photobiont partner of Peltigera and Collema cyanolichens, was included for comparison. MIR spectra were acquired from lichen organic extracts between 3800–950 cm −1 using a chalcogenide infrared fibre optical device. Principal Component Analysis (PCA) and PCA-LDA (PCA-Linear Discriminant Analysis) based on the concept of variable clustering has been applied to absorbance MIR second derivative spectra for classification of the 11 species. The method succeeded in separating all lichen species and in identifying the major compounds. Moreover, the signature of the sample was specific of each lichen suggesting that minor compounds played a role. Our data showed that FEWS optical sensor profiling is a rapid, efficient and convenient tool for metabolic profiling and suggest that it can be used: (i) in chemotaxonomic approaches, (ii) in processes for certification requirements in active compounds availability, and (iii) in identifying new biosourcings in so far non-investigated lichen species.